Het Nederlandbeeld van de tot de galeien veroordeelde Hongaarse predikanten* - Bujtás, László Zsigmond (Acta Neerlandica, 2017)
From already published letters of Hungarian Protestant ministers damned to the Neapolitan galleys by a special law court at Pozsony (Bratislava) in 1675 to prominent Dutch persons, from almost the galleys turns out that they called them, consequently the Netherlands as defenders of the truth belief (fides orthodoxa) who felt solidarity with fellow-Protestants (especially the Reformed ones) abroad, were ready to support them in their struggle to preserve their religious freedom and to assist to build the Church of God everywhere. The article also analyses unpublished works of the Protestant ministers and their supporter at Venice during their slavery and after their liberation by admiral Michiel de Ruyter in 1676. In these documents the same image of the Netherlands can be found but also two more epitatheta ornantia can be observed: they called the members of the States General, respectively the country as the nourishers of the Church and the greatest defenders of the truth of the Gospel.